Sustainable management of the supply chain based on fuzzy logic - Barcellos de Paula, Luciano (2021)
Companies face a number of management challenges, and decision makers must adopt new approaches that consider sustainable development in their operations. In this context, the article aims to address sustainable supply chain management and propose solutions based on a fuzzy logic. Three distance measurement algorithms are applied to evaluate and classify suppliers in a consumer goods industry. The results demonstrate the usefulness of the algorithms in decision-making and bring a contribution to the sustainable development of companies. Furthermore, it supports future studies on sustainable management, the supply chain, and the application of algorithms to sustainability.